Notaries-chancellors in late medieval Dubrovnik: Peer reviewed article (Italian Review of Legal History, 2021)
The relationship between public writings and the legal status of notaries in medieval Ragusa (today Dubrovnik) is the topic of this paper. As communal city located outside the borders of the Roma-Germanic Empire, the evolution of the notary followed there different and ever-changing paths, although the model drawn up by the Bolognese school exercised an increasingly irresistible charm with the beginning of Early Modern era. The most relevant result of this peculiar experience, was the assimilation between notaries and chancellors in an unique profession, fully inserted within the state bureaucracy. Thanks to their law-studies graduation at Italian universities, the government decided at the end of 13th century to reserve the notary profession for jurists from peninsula.
Keywords: Notaries; Chancellors; Ragusa-Dubrovnik; Dalmatia; Venice; Law history